2020
DOI: 10.1111/jgh.15221
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: The effect of vitamin E supplementation in adult patients with non‐alcoholic fatty liver disease

Abstract: Background and Aim Νon‐alcoholic fatty liver disease (NAFLD) is estimated to be the most common cause of end‐stage liver disease in the next years. Vitamin E has shown beneficial effects as a possible “scavenger” of oxidative stress products, which play a major role in pathogenesis of the disease. The purpose of the present meta‐analysis is to investigate the effects of vitamin E supplementation in biochemical and histological parameters in adult patients with NAFLD. Methods Literature search was performed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 34 publications
2
31
0
8
Order By: Relevance
“…Moreover, reducing oxidative stress (e.g. by vitamin E or metformin) also alleviates lipotoxicity [96,116]. Furthermore, the use of chemical chaperones [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, reducing oxidative stress (e.g. by vitamin E or metformin) also alleviates lipotoxicity [96,116]. Furthermore, the use of chemical chaperones [e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of de novo lipogenesis by αT was also observed in vitro, where it was dependent on the antioxidant function of αT, highlighting once again the interplay between oxidative stress and steatosis 148 . A meta‐analysis of eight clinical trials (including 465 NAFLD patients) showed an overall benefit of vitamin E‐supplementation on histological parameters of NAFLD that appear to be especially pronounced in patients with NASH 149 . None of the clinical trials reported any adverse events attributed to treatment 141–143 …”
Section: Role Of Biofactors In Nonalcoholic Fatty Liver Diseasesmentioning
confidence: 93%
“…In addition to dietary and exercise intervention, vitamin E supplementation is well-recognized as an anti-NAFLD therapeutic nutrient in both adults and children (148)(149)(150). Meta-analysis demonstrated that vitamin E was effective in ameliorating the biochemical and histological characteristics of adult patients with NAFLD, especially NASH (150). In children with NASH, a double-blind, placebo-controlled, randomized trial found that vitamin E treatment did not reduce ALT levels but significantly improved histologic outcomes (148).…”
Section: Conventional Therapeutic Approach To Nafld and The Interaction With Gut Microbiotamentioning
confidence: 99%